2021
DOI: 10.1096/fj.201903129rrr
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of gut microbiota improves post‐myocardial infarct tissue repair in rats via butyric acid‐mediated histone deacetylase inhibition

Abstract: The complex and dynamic population of gut microbiota exerts a marked influence on the host during homeostasis and disease. Imbalance of gut microbiota metabolites may lead to cardiac dysfunction in patients with heart failure, which is related to myocardial infarction(MI) severity. However, the role of gut microbiota in the repair process after MI has rarely been reported. To explore the role of gut microbiota in MI repair and its underlying mechanism, we mixed antibiotics in drinking water to interfere with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Additionally, some studies reported that gut microbiota possibly affected the post-MI acetylation levels and tissue repair by influencing butyric acid production (Song et al, 2021). These results prove the role of HDAC4 inhibition in promoting CSC-derived cardiac regeneration and improving cardiac function recovery.…”
Section: Histone Modifications and Hdacs In MImentioning
confidence: 58%
“…Additionally, some studies reported that gut microbiota possibly affected the post-MI acetylation levels and tissue repair by influencing butyric acid production (Song et al, 2021). These results prove the role of HDAC4 inhibition in promoting CSC-derived cardiac regeneration and improving cardiac function recovery.…”
Section: Histone Modifications and Hdacs In MImentioning
confidence: 58%
“…Studies showed that a decrease in Akkermansia is related to obesity and diabetes, and the introduction of Akkermansia could reverse the metabolic disorder and improve inflammation in diabetics and obese patients [ 33 ]. However, studies have also shown that the increase in Streptococcaceae is significantly correlated with myocardial infarction [ 34 ]. After PFM-SR61-2 intervention, the beneficial bacteria Bifidobacteriaceae significantly displayed an increased abundance.…”
Section: Resultsmentioning
confidence: 99%
“…Butyric acid, a SCFA produced daily by gut microbiota, has been shown to benefit cardiovascular disease models. It has been reported that gut microbiota affected the acetylation level and tissue repair process after myocardial infarction by affecting the production of butyric acid ( 28 ). Previous studies have shown that butyrate intervention decreased potentially pathogenic species, including Desulfovibrionaceae , which was a potential group of endotoxin producers ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%